Tracing the theoretical path of my teaching experience at a private English institute - Caro Ávila, Angie Milena (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This paper reflects on the connections between theory and practice in a private English institute in which students follow seven different stages to complete one lesson. The objective of the researcher, an in-service English teacher, was to analyze the institute’s theoretical principles underlying each of the seven stages. These stages were studied in terms of the theories or approaches which guided the different stages in teaching and learning the English language. In order to provide an informed review of the theory and its application in practice, specialized authors, such as Richards and Rodgers (1993) or Harmer (2013), were revisited. Throughout the paper, the benefits and drawbacks students received when using the identified theories or approaches in their classes are reflected upon. Additionally, the researcher’s professional development during the steps she guided is critically analyzed.